2007
DOI: 10.1681/asn.2006101145
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Nephrin According to Glomerular Size in Early Diabetic Kidney Disease

Abstract: Diabetic nephropathy (DN) is clinically characterized by proteinuria. Many studies tried to demonstrate a relationship between proteinuria and changes in nephrin in various forms of glomerular diseases including DN, but the results are not consistent. Glomerular hypertrophy occurs in DN, yet hypertrophy does not develop in all glomeruli concurrently. For investigation of the differences in nephrin expression according to glomerular size, glomeruli were isolated from 10 control and 10 streptozotocin-induced dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…In experimental animal models of diabetes, nephrin expression has been reported to be either upregulated or downregulated (10,(37)(38)(39). In our diabetic mice, nephrin was upregulated when compared with control nondiabetic animals, and the podocyte overexpression of sFlt-1 did not affect this upregulation.…”
Section: Sflt-1 Ameliorates Diabetic Glomerulopathymentioning
confidence: 57%
“…In experimental animal models of diabetes, nephrin expression has been reported to be either upregulated or downregulated (10,(37)(38)(39). In our diabetic mice, nephrin was upregulated when compared with control nondiabetic animals, and the podocyte overexpression of sFlt-1 did not affect this upregulation.…”
Section: Sflt-1 Ameliorates Diabetic Glomerulopathymentioning
confidence: 57%
“…The loss of podocytes is thought to be a key event in DN. It has been reported previously that mice and humans with diabetes exhibit a disruption of nephrin expression (27,28). Furthermore, a previous study showed that podocytes expressing a mutated form of nephrin displayed increased apoptosis in response to serum starvation (29), suggesting a relationship with the absence of nephrin signaling actions.…”
Section: Discussionmentioning
confidence: 89%
“…Glomerulomegaly is also observed in the kidneys of diabetic nephropathy and hypertensive kidney [1,6,8]. An increase in glomerular volume is usually the consequence of glomerular hyperfiltration, and can be associated with expansion of capillary loops [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in glomerular volume is usually the consequence of glomerular hyperfiltration, and can be associated with expansion of capillary loops [8,9,10]. Obesity can accelerate renal dysfunction in patients with glomerulonephritis such as IgA nephropathy (IgAN).…”
Section: Introductionmentioning
confidence: 99%